Family Accommodation Scale for Sensory Over-Responsivity: A Measure Development Study - Ben-Sasson, Ayelet; Podoly, Tamar Yonit; Lebowitz, Eli (Frontiers in Psychology, 2022)
Family accommodation refers to the attempt of family members (most often parents) to prevent their child’s distress related to psychopathology. Family accommodation can limit meaningful participation in personal and social routines and activities. Accommodation has been studied extensively in the context of childhood anxiety and has been linked to greater impairment, and poor intervention outcomes. Like anxiety, sensory over-responsivity (SOR) symptoms are associated with heightened distress and thus, may also be accommodated by family members. The current study describes the validation of a new pediatric family accommodation scale for SOR. Parents of 301 children ages 3-13 years completed an online survey, of which 48 had medical or developmental conditions. The survey included the Child Sensory Profile 2 and the newly developed Family Accommodation Scale for Sensory Over-Responsivity (FASENS). Three Sensory Profile 2 scores were analyzed: SOR, sensory under-responsivity and sensory seeking. The FASENS consists of 18 items; 12 describing the frequency of accommodation behaviors and 6 describing the impact of the accommodation on the wellbeing of the family and the child. Results indicated that the FASENS has high internal reliability (α=.94) as well as a significant 3-factor confirmatory model fit: (1) accommodations (i.e., avoidance and changes), (2) family impact, and (3) child impact. FASENS scores significantly correlated with SOR symptoms (r=.52-.60, p<.001). However, they also correlated with under-responsivity and seeking (r=.33-.42, p<.001). Parents of children with health conditions had significantly higher FASENS scores (p<.002), which corresponded with their child’s significantly higher sensory scores (p<.001). Family accommodations for SOR occur to some extent in the general population, but their prevalence and impact are significantly greater when the child has a health condition, in addition to SOR. Additional research is needed to explore whether these accommodations are adaptive or whether families and children would benefit from learning to reduce them, as with anxiety.